English Encountered by Icelandic Children. Is English becoming the second language of Iceland’s youth? - Þóranna Hrönn Þórsdóttir 1985- (2012)
The aim of this essay is to study the status of English in Iceland, specifically the exposure Icelandic children encounter through various types of media. In order to achieve this goal, two types of studies were conducted to determine the amount of English input Icelandic children encounter. First, information was gathered from the media providers in Iceland to shed light on the amount of exposure, and secondly, a survey was conducted with children of the ages eight and nine to determine how many times the children encountered English through media in their private time, what types of media they consumed and how much they used English outside school. In addition, the status of English as a global language is discussed along with a distinction between a foreign language and a second language. Due to high exposure of English through media, young Icelanders may be moving closer to speaking English as a second language than as a foreign language. The exposure is mostly of conversational English while the English needs seem to be more of an academic and formal nature. The relationship between exposure, formal English instruction and actual English proficiency needs of Icelandic children needs further investigation.